Peran Orang Tua pada Anak dari Latar Belakang Keluarga Broken Home - Salsabila Priska Adristi (Lifelong Education Journal, 2021)
This article aims to look at the role of parents for their children where their family situation is not fine or can be said to be a broken home. People still think that children from broken home families are naughty children and cannot be managed so that in the end they will only become community waste. The existence of this stigma needs to be changed because not all children from broken home families are naughty and cannot be regulated. There are also quite a number of children from broken home families who have made achievements in their schools. Therefore, there needs to be encouragement and motivation for both parents so that children do not experience mental shocks due to separation from their parents. This research was conducted with a qualitative method, with data collection techniques used, namely the study of literature in related journals and articles. The results obtained in this article are in the form of forms of encouragement and motivation given by each father and mother in carrying out their role as parents.